Checklist of the subfamily Adoncholaiminae Gerlach and Riemann, 1974 (Nematoda: Oncholaimida: Oncholaimidae) of the world: genera, species, distribution, and reference list for taxonomists and ecologists - Shimada, D. (Biodiversity Data Journal, 2016)
Adoncholaiminae is one of the seven subfamilies in the free-living aquatic nematode family Oncholaimidae. Nematodes in Adoncholaiminae are found from various water environment of the world. However, a checklist of all Adoncholaiminae species including full literature, especially information of experimental (not taxonomic) works, has not been updated for more than 40 years. A revised checklist of the subfamily Adoncholaiminae of the world is provided. It contains 31 valid and 13 invalid species names in four genera with synonyms, collection records, and full literature from 1860's to 2015 for each species. A literature survey of total 477 previous papers was conducted in this work, and 362 of them are newly added to checklist.